Between the pleasure of the text and the image. The case of Alberto Fuguet - Kruk, Adam (Hybris, 2025)
In 1988, a referendum was held in which Chileans decided to remove General Pinochet’s regime from power. A year later, the first free elections since 1970 were held and the political transition began, making room for new cultural currents to manifest themselves more freely in the changed reality. One of the first high-profile proposals at the time was made by the Chilean writer and director Alberto Fuguet, who made his debut in 1990, sharply attacking magical realism in Latin American literature (which he saw as an outdated) and proclaiming the need for a culture better suited to a Chile at the time of globalization. The aim of the paper is to show how Fuguet fills his literary works with popular culture, above all with film, which is transcribed or perhaps rather transformed into text, but also how he places text in his films – not through adaptation strategies, not only in dialogues or songs, but also in a typographic sense. Investigating the tension between the pleasure of the text and the pleasure of the image in the work of Fuguet, who is active in both fields, should also allow for a better understanding of the cultural changes taking place in the Chilean landscape (and beyond) in recent decades.